CLIMATIC CHANGES AND ITS EFFECTS ON HUMAN HEALTH- A REVIEW - L, Reethiga; R V, Geetha; T, Lakshmi (International Journal of Psychosocial Rehabilitation, 2020)
Climatic changes are the totality of the climatic variability and changes which consists of its descriptions, causes, implications and interactions. In the last 5 decades, human activities, particularly the burning of fossil fuels have released sufficient quantities of carbon dioxide and other greenhouse gases and this traps the additional heat in the lower atmosphere which therefore affect the global climate and temperature. Each of these effects have caused significant changes in the human health cycle and causes harm to our body and environment Around 40 articles from online databases like PubMed and Google Scholars are taken. The articles which are related to the topic are taken. The relevant articles are taken and discussed. The various effects of climate changes are discussed. The direct and indirect changes, effect on infectious diseases, population and the major risk factors are assessed. The climatic changes are the mainstream issue of today’s generation. Potentially huge health defects affect the society and people in it. Hence measures should be taken to prevent climatic changes and global warming.